Patient and Provider Perspectives Regarding Enrollment in Head and Neck Cancer Research. (10th December 2019) - Shuman, Andrew G.; Gornick, Michele C.; Brummel, Collin; Kent, Madison; Spector‐Bagdady, Kayte; Biddle, Elliot; Bradford, Carol R.; Brenner, J. Chad
Abstract : Objective: The advent of precision oncology complicates how clinicians and participants understand how clinical care and research interface. Here we examine how key stakeholders perceive the utility of, and evaluate the decision to participate in, genomic sequencing head and neck cancer research. The goal of this study was to highlight unique considerations for our community as this type of research proliferates across the country. Study Design: Prospective multimethod qualitative and quantitative embedded ethics protocol. Setting: Single‐institution National Cancer Institute–designated academic cancer center. Subjects and Methods: Multimethod study using paired surveys and semistructured interviews among patients and providers involved in a prospective precision head and neck oncology sequencing protocol (116 survey patient‐participants, response rate 82%) with 18 interviewees. Results: Participants were generally enthusiastic about enrollment in research, both to help future patients and as a way of giving back to the community. They described reliance on information from and trust in their cancer doctor regarding the decision to participate in research, but paradoxically there was discordance in how doctors and patients reported their respective influence in the decision‐making process. Clinicians also stressed the importance in separating clinical and research‐informed consent processes, although patients did not describe this tension. Conclusion: As we enter an era of increasing personalized medicine and targeted therapies, the relationship between clinicians, scientists, and patients plays a larger role in how we individualize and contextualize cancer research. Our data are another step toward the ultimate goal of respecting and protecting patients as participants in head and neck translational oncology.